2015
DOI: 10.1063/1.4932578
|View full text |Cite
|
Sign up to set email alerts
|

Contributed Review: Absolute spectral radiance calibration of fiber-optic shock-temperature pyrometers using a coiled-coil irradiance standard lamp

Abstract: Development of a fast fiber-optic two-color pyrometer for the temperature measurement of surfaces with varying emissivities Rev. Sci. Instrum. 72, 3366 (2001); 10.1063/1.1384448 This article is copyrighted as indicated in the article. Reuse of AIP content is subject to the terms at: http://scitationnew. We describe an accurate and precise calibration procedure for multichannel optical pyrometers such as the 6-channel, 3-ns temporal resolution instrument used in the Caltech experimental geophysics laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 75 publications
(123 reference statements)
2
10
0
Order By: Relevance
“…Third, the initial temperature of MgO was monitored at the back surface of the capsule and, therefore, was most accurately known there. Fourth, our detailed calibration studies [26] revealed that the difference between the static and dynamic response of our amplified photodetectors decreased as the input light pulse duration increased. Therefore the errors in the corresponding correction factors are minimized at the end of useful radiance records.…”
Section: A Shock Temperature Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Third, the initial temperature of MgO was monitored at the back surface of the capsule and, therefore, was most accurately known there. Fourth, our detailed calibration studies [26] revealed that the difference between the static and dynamic response of our amplified photodetectors decreased as the input light pulse duration increased. Therefore the errors in the corresponding correction factors are minimized at the end of useful radiance records.…”
Section: A Shock Temperature Analysismentioning
confidence: 99%
“…[33]. A comprehensive review of the Caltech sixchannel pyrometer operation and calibration can be found elsewhere [26]. Therefore we give only a brief description of the most essential issues, shock target parameters, and newly developed procedures for the data acquisition and analysis.…”
Section: Experimental Approachmentioning
confidence: 99%
See 3 more Smart Citations